The Relationship Between serum PTH ,potassium (K+), calcium (Ca2+), blood phosphate (PO4), parathyroid hormone (PTH), albumin (ALB)levels and Orthostatic Hypotension in Hemodialysis Patients: Influencing Factors of OH After Hemodialysis - Chen, Yuling (Journal of Medical Biochemistry, 2025)
Introduction: orthostatic hypotension (OH) in maintenance hemodialysis (MHD) patients is a frequent chronic complication. OH may lead to inadequate dialysis, cardiovascular complications, and death. This work explored the Relationship Between serum PTH ,potassium (K+), calcium (Ca2+), blood phosphate (PO4), parathyroid hormone (PTH), albumin (ALB)levels and Orthostatic Hypotension in Hemodialysis Patients.Material and Methods: 121 MHD patients were enrolled, and their clinical data were acquired. They were categorized into a control (Ctrl) group (normal patients) and an observation (Obs) group (OH patients) based on the diagnostic criteria for OH. Differences in clinical data between patients in different groups were compared, and binary logistic regression (BLR) analysis was performed to assess contributing factors.Results: among the 121 MHD patients, 40 experienced orthostatic hypotension, resulting in an incidence of 33.06%. In contrast to the Ctrl group, the Obs group exhibited increased age, supine systolic blood pressure (SBP), diabetes prevalence, and parathyroid hormone (PTH) levels, as well as decreased blood pressure (BP) at 1 minute and 3 minutes of standing, serum albumin (ALB), and triglyceride (TC) levels (P
Keywords: serum PTH ,potassium (K ), calcium (Ca2 ), blood phosphate (PO4), parathyroid hormone (PTH), albumin (ALB) ,Hemodialysis,; orthostatic hypotension; diabetes; serum albumin; independent risk factors